Transvenous approach for the treatment of direct carotid cavernous fistula following Pipeline embolization of cavernous carotid aneurysm: a report of two cases and review of the literature. (29th July 2014) - Lin, Li-Mei; Colby, Geoffrey P; Jiang, Bowen; Pero, Guglielmo; Boccardi, Edoardo; Coon, Alexander L
Abstract : Flow diverters are increasingly used for the endovascular treatment of cerebral aneurysms. A rare complication from flow diversion is delayed aneurysm rupture, which can lead to carotid–cavernous fistula (CCF) in the setting of cavernous carotid aneurysms (CCAs). Direct CCFs pose unique management challenges, given the lack of transarterial access to the fistula. We present two cases of direct CCFs following treatment of CCAs with the Pipeline embolization device (PED). Case 1 was a middle-aged patient with a symptomatic 10 mm wide-necked left CCA. Six weeks after PED treatment the patient developed diplopia secondary to direct CCF. Case 2 was a middle-aged patient with a symptomatic 17 mm left CCA treated with PED. One-month follow-up angiography demonstrated a direct CCF. Both patients underwent successful coil embolization of the CCF through a transvenous approach. Direct CCF formation following PED deployment for CCA is a rare complication. Parent vessel sacrifice may be avoided with transvenous occlusion of the fistula.